HASIL TANAMAN KENTANG (Solanum tuberosum, L.) VAR. GRANOLA L. (G1) PADA BERBAGAI KONSENTRASI Trichoderma sp. DAN MEDIA TANAM - Agung Widi Saputro; Hadi Rianto; Agus Suprapto (Universitas Tidar, 2019)
A research to study potato yield (Solanum tuberosum, L.) var. Granola L. (G1) at various concentrations of Trichoderma sp. and planting media, has been done in April to July 2018 in Bandongan Wetan, Ngablak Village, Ngablak District, Magelang Regency. The altitude is 1300 meters. The research method used factorial experiments (4 x 3) arranged in a randomize complete block design, repeated 3 times. The first factor is concentration of Trichodermsa sp. which consists of : 0 ml/l, 5 ml/l, 10 ml/l, and 15 ml/l. The second factor is type of planting media which consists of : soil + cow manure (2 : 1), soil + goat manure (2 : 1), and soil + chicken manure (2 : 1). The results showed that increasing the concentration of Trichoderma sp. till 15 ml/l don’t give an effect an all parameters. Soil + goat manure (2 : 1) increases yield per m2 and soil + chicken manure (2 : 1) increases harvest index. Different concentration of Trichoderma sp. on different planting media gave the regular result on all observed parameters.